Efektivitas Metode Imla’ Dalam Peningkatan Keterampilan Menulis Pada Pembelajaran Bahasa Arab di Madrasah Diniyyah Takmiliyah Awaliyah Al-Haqq - Putri, Sharla Yusfirman; Nursholihah, Asri Fitriyani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the application of the imla' method in learning Arabic writing skills at Madrasah Diniyyah Takmiliyah Awaliyah (MDTA) Al-Haqq. The imla' method is an effective approach to teaching writing in Arabic, involving the teacher reading the lesson material and students being asked to write it in notebooks. The research results show that the application of the imla' method is very helpful in improving Arabic writing skills. Students feel that this method makes it easier for them to learn to write Arabic because it can train them directly. This method encourages students to be more active, independent and competent in writing, and increases their interest in learning. Thus, the imla' method is very useful in training students' concentration and developing students' listening skills..